Perianal Herpes Zoster with Diabetes Mellitus: A Rare Case Report - Kelvin Kelvin; Cayadi Sidarta Antonius (Indonesian Journal of Global Health Research, 2026)
Herpes zoster (HZ) is caused by the reactivation of latent varicella-zoster virus and most commonly affects the thoracic and trigeminal dermatomes. Involvement of the sacral dermatomes, particularly with perianal extension, is rare and can mimic various anorectal disorders, leading to delayed diagnosis in elderly patients with comorbidities. In this case report, herpes zoster in the perianal area significantly disrupted the patient's daily activities, requiring prompt diagnosis and management. A 78-year-old female presented with blisters accompanied by pain, burning, and tingling in the left buttock area extending to the anus. The dermatologic findings included multiple vesicles to bullae on an erythematous base containing clear fluid in a zosteriform arrangement, discrete to confluent, crusted form. A Tzanck test revealed multinucleated giant cells. The primary therapy consisted of oral acyclovir and mupirocin ointment. Herpes zoster involving the sacral to perianal dermatomes (S2-S4) can cause various functional complications, including neuritis characterized by sensory and motor deficits, which can affect the patient's daily activities. Antiviral treatment within the first 72 hours can help minimize complications. Pain should be controlled to prevent worsening the patient's quality of life. Early diagnosis and treatment, along with vaccination, can reduce morbidity and prevent complications, especially disruption of daily activities in patients with perianal HZ.